Building Philippine SMEs Resilience to Natural Disasters - Marife M. Ballesteros; Sonny N. Domingo (Philippine Institute for Development Studies (PIDS), 2015)
Disasters are bad for business specifically for small and medium enterprises (SMEs). These catastrophic events can compromise capital, logistics, product market, and labor, which compromise business continuity and recovery. Physical damage and disruptions in supply and labor can cause temporary business closure while structural repairs to buildings and recovery or replacement of damaged equipment needed to restore operations require large amount of resources. The adverse impact may not only be short term but can have medium- to long-term effects. Unfortunately, the disaster risk reduction and management (DRRM) framework of the government has not been effectively translated into local and sectoral (or business) plans. Philippine SMEs thus are highly vulnerable, have weak adaptability and limited access to a broader set of coping strategies. This paper recommends strategic policies to embed DRRM into the business sector and the role of APEC in promoting SME resilience in the region.
Keywords: 330; Philippines; business; disasters; resilience; micro; small; and medium enterprises (MSMEs)